Long-term outcomes after revascularization surgery for adult moyamoya disease: Protocol for systematic review and meta-analysis - Sha Wang; Jingjin Zhao; Xinzhu Chen; Liangzhen Zhou; Wenyao Cui (PLoS ONE, 2025)
Introduction Moyamoya disease (MMD) commonly presents with cerebral ischemia or hemorrhage. Revascularization surgery, including direct, indirect, and combined bypasses, remains the mainstay of MMD treatment aiming to reduce stroke recurrence. However, the long-term outcomes of these interventions are still controversial. Herein, we designed the protocol for a systematic review and meta-analysis comparing the three different revascularization surgeries in adult MMD patients for more than 5 years long-term outcomes. Methods Our systematic review and meta-analysis protocol follows the PRISMA-P guidelines. Bypass surgeries for MMD will be included only if the follow-up time is more than 5 years. The primary outcome is the incidence of recurrent cerebral ischemia or hemorrhage. The secondary outcomes include functional outcomes evaluated by the Moyamoya Disease outcome category, mortality, and angiographic outcomes such as bypass patency, and collateral formation. Results Studies on the postoperative outcomes of revascularization surgeries to treat adult MMD patients will be included and analyzed. This systematic review and meta-analysis will offer evidence to clinicians and researchers on the long-term outcomes of revascularization surgeries in adult MMD patients and help to optimize the selection of bypass modality.